The Humanitarian Regime of Sovereignty: INGOs and Iraqi Migration to Syria - Hoffmann, Sophia (Refuge: Canada’s Journal on Refugees, 2012)
This article considers the activities of international, humanitarian NGOs in Syria focused on Iraqi migrants. The analysis questions how these INGOs were positioned towards modern state sovereignty, and sovereignty’s particular constructions of territory, population, and government. Arguing that most INGOs operated firmly within the social relations stipulated by modern sovereignty, the article uses rich ethnographic data to demonstrate how INGO activities treated Iraqis according to sovereign exclusions and ideas about citizenship, even though Iraqi life in Syria visibly contradicted these ideas. Only smaller, amateur INGOs that stood outside of the professional humanitarian sector were found to work outside of sovereignty’s norms.